2023
DOI: 10.1063/5.0141113
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-current density spin-torque diodes with high sensitivity

Abstract: Spin-torque diodes (STDs) offer the possibility of using spin torque to generate rectification voltage with promising applications in microwave detecting, energy harvesting, and neuromorphic computing. Here, we demonstrate a highly sensitive STD with ultralow current density based on a magnetic tunnel junction with perpendicular magnetic anisotropy. At zero magnetic field, a high sensitivity exceeding 3785 V/W is obtained with a low current of −20 μA, corresponding to a current density of ∼105 A/cm2, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…At the same time, if the frequency of the RF current applied to the MTJ is close to the precession frequency of the free layer, the injection locking will occur and the device will generate high rectification voltage. 15,22,27) Figure 2(a) indicates the dc bias current dependence of the device resistance under the optimum fields of H ext = −200 Oe. It can be seen that with the current increasing, the resistance of the device arrives at an IR state under a certain current range, which indicates that this device can achieve high microwave detection sensitivity through the injection phase locking mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, if the frequency of the RF current applied to the MTJ is close to the precession frequency of the free layer, the injection locking will occur and the device will generate high rectification voltage. 15,22,27) Figure 2(a) indicates the dc bias current dependence of the device resistance under the optimum fields of H ext = −200 Oe. It can be seen that with the current increasing, the resistance of the device arrives at an IR state under a certain current range, which indicates that this device can achieve high microwave detection sensitivity through the injection phase locking mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The growth rates were extracted based on the thicknesses extracted from the SIMS samples and the growth time for each sublayer of the SIMS stack. [11] 0.3°LA-MOCVD GR [μm h À1 ] [11] 4 °C-MOCVD GR comparisons were evaluated using a field-emission gun (FEG)scanning electron microscopy (SEM) (Thermo Scientific Apreo FEG-SEM). To quantitatively analyze the concentrations of impurities incorporated within the GaN films grown at different growth conditions, quantitative SIMS depth profiling was carried out for Si, O, C, and H impurities.…”
Section: Methodsmentioning
confidence: 99%
“…[8,10] Previous studies have shown that C incorporation increases more significantly when the growth rates are above 5 μm h À1 . [8,11] A theoretical model has been developed to correlate the impurity C incorporation against GaN growth rate, which suggests that C incorporation can be significantly suppressed using GaN substrates with higher offcut angles. [11] In addition, prior studies of GaN films grown on m-plane GaN substrates have shown a reduction in C incorporation with an offcut angle of 5°toward the -c direction.…”
mentioning
confidence: 99%
See 2 more Smart Citations